Design Specifications of Augmentative and Alternative Communication Apps for Individuals with Autism Spectrum Disorder - Polat, Hamza; Delialioglu, Omer (International Journal of Technology in Education, 2023)
The literature has emphasized the positive impact of mobile technologies with augmentative and alternative communication (AAC) apps for enhancing the functional communication skills of individuals with autism spectrum disorders (ASD). Although various AAC apps are available, the system design of such apps presents assorted challenges, particularly for those with ASD in different cultures. Designing useful and engaging apps by considering the affordances of mobile technologies and the characteristics of individuals with ASD may contribute to the success of interventions. In this regard, the purpose of this study is to examine the design specifications of AAC apps based on the considerations of subject-matter experts from an instructional system design (ISD) perspective. The current research employed a design-based research framework, including different methods. An AAC app named as EBA was developed by following design specifications as suggested by the field experts to answer the research questions. The results of the study revealed several enhancements in usability, flexibility, and feasibility issues of AAC apps, and highlighted the importance of (a) personalized apps, (b) simple user-interface, (c) hierarchical representation of visuals, (d) responsive apps, (e) help and documentation, and (f) parent control service. Directions for future research are proposed.